The Interplay of Cognition and Emotion in Brain-Based Social Studies Classroom - John Albert R Dela Rosa (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study investigates how students' cognition and emotion are interrelated and interconnected in learning Social Studies through a brain-based learning approach. The results will contribute to the academic discourse on the role of brain science in transforming classroom practices in Social Studies to achieve the desired learning outcomes. Methodology: A case study methodology was utilized to explore how brain-based Social Studies lessons influence students' cognitive and emotional responses. Data were collected through interviews, focus group discussions, and creative assessment tools such as emoticons, numerical ratings, and metaphors, enabling a comprehensive understanding of students' perceptions, engagement levels, and overall learning experiences within the classroom context. Main Findings: Social Studies is a value-based discipline that necessitates the development of both cognitive and emotional skills among students. Therefore, the integration of emotion in teaching Social Studies should align with the subject’s learning objectives. It should begin with enjoyment to activate students' brains, followed by surprise to help them see connections, and conclude with optimism, demonstrating how their learning can be applied to real-life situations. This dual focus is essential for fostering civic participation and cultivating active citizenship. Novelty/Originality of this study: Brain-based learning, as an emerging approach in teaching Social Studies, posits that emotion and cognition are intertwined and inseparable. It provides solid scientific explanations for how the brain learns and achieves the desired learning outcomes of the subject. This approach may offer a long-awaited solution to the longstanding perception of Social Studies as a dull and unengaging subject.